Peri‐implant bone adaptations to overloading in rat tibiae: experimental investigations and numerical predictions. Issue 11 (11th February 2016) - Piccinini, Marco; Cugnoni, Joel; Botsis, John; Ammann, Patrick; Wiskott, Anselm
Abstract: Objectives: (i) To assess the effects of mechanical overloading on implant integration in rat tibiae, and (ii) to numerically predict peri‐implant bone adaptation. Materials and methods: Transcutaneous titanium implants were simultaneously placed into both tibiae of rats ( n  = 40). After 2 weeks of integration, the implants of the right tibiae were stimulated daily for 4 weeks with loads up to 5N (corresponding to peak equivalent strains of 3300 ± 500 με). The effects of stimulation were assessed by ex vivo mechanical tests and quantification of bone mineral density (BMD) in selected regions of interests (ROIs). Specimen‐specific finite element models were generated and processed through an iterative algorithm to mimic bone adaptation. Results: Bilateral implantation provoked an unstable integration that worsened when mild (2–4N) external loads were applied. In contrast, a stimulation at 5N tended to "counterbalance" the harmful effects of daily activity and, if applied to well‐integrated specimens, significantly augmented the implants' resistance to failure (force: +73% P  < 0.01, displacement: +50% P  < 0.01 and energy: +153% P  < 0.01). Specimen‐specific numerical predictions were in close agreement with the experimental findings. Both local and overall BMD variations, as well as the implants' lateral stability, were predicted with small errors (0.14 gHA/cm 3 and 0.64%, respectively). Conclusions: The rats' daily activity detrimentally affects implant integration. Conversely, external stimulations of large magnitudes counterbalance this effect and definitively improve integration. These changes can be predicted using the proposed numerical approach.